Factors a ecting the job performance of church ocers in the borough of Brooklyn in the Northeastern Conference of Seventh-Day Adventists in New York - Basurto Gutiérrez, Karla Saraí; Brathwaite, Mark H. (Anuario de Investigación UM, 2020)
The empirical model in which organizational commitment, recognition, motivation, and training are predictors of job performance, as perceived by Church Ocers of the Northeastern Conference of Seventh-day Adventists in the Borough of Brooklyn, New York, USA.